2021
DOI: 10.3390/ijms22031414
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Activity of Staphylococcus epidermidis Induces Collagen Type I Production through FFaR2/p-ERK Signaling

Abstract: Collagen type I is a key structural component of dermis tissue and is produced by fibroblasts and the extracellular matrix. The skin aging process, which is caused by intrinsic or extrinsic factors, such as natural aging or free radical exposure, greatly reduces collagen expression, thereby leading to obstructed skin elasticity. We investigated the effective fermentation of Cetearyl isononanoate (CIN), a polyethylene glycol (PEG) analog, as a carbon source with the skin probiotic bacterium Staphylococcus epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Both bene cial and harmful effects of butyric acid on humans have been documented (24). Thus, we examined how butanoate metabolism in humans or skin bacteria metabolized 28 constituents detectable in sweat.…”
Section: Resultsmentioning
confidence: 99%
“…Both bene cial and harmful effects of butyric acid on humans have been documented (24). Thus, we examined how butanoate metabolism in humans or skin bacteria metabolized 28 constituents detectable in sweat.…”
Section: Resultsmentioning
confidence: 99%
“… Staphylococcus epidermidis is a ubiquitous inhabitant of human skin and plays a crucial role in maintaining skin homeostasis. Various studies have shown that S. epidermidis is the guardian of skin health, promoting skin immunity, repair, and antimicrobial defense ( 1 8 ). S. epidermidis CCSM0287 was isolated from the healthy facial skin of a Chinese woman.…”
Section: Announcementmentioning
confidence: 99%
“…According to [38], the main difference can be seen in the collagen proteins in a membrane protein complex in dermal fibroblasts during skin aging, i.e., collagen type I, which accounts for around 80% of the overall collagen in the adult human dermis and its content could indicate degradation. It is shown that Se-enriched tuna enhances collagen synthesis and promotes the proliferation of fibroblasts having anti-aging and anti-wrinkle effects [39].…”
Section: Cosmeceutical Effect Of Selenized Hydrolysatesmentioning
confidence: 99%